Consistency of recommendations for pharmacotherapy of rheumatoid arthritis - Hu, Yue; Han, Yunze; Ma, Yan; Fan, Shumei; Wang, Xue; Fu, Xinyu; Hu, Xiaopeng; Luo, Xufei; Ma, Yanfang; Xun, Yangqin; Yang, Nan; Wen, Chengping; et al. (Frontiers in Pharmacology, 2022)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory arthropathy. Recommendations for RA, specifically on pharmacotherapy, are essential in clinical practice. However, the direction and strength of recommendations are controversial across current clinical practice guidelines (CPGs) of RA. Objective: To systematically analyze the consistency of recommendations regarding pharmacotherapy of RA across CPGs. Methods: 11 electronic databases and websites were comprehensively searched from inception to March 14th, 2022, to identify CPGs for diagnosis, therapy, and management of RA. Unambiguous and discrete specifications of the population-intervention-comparison (PIC) framework were used to classify the recommendations. Based on the PIC framework, consistency analyses across CPGs on pharmacotherapy of RA were performed. Two researchers reached a consensus on coding the direction and strength of each recommendation. Results: Finally, 26 CPGs were included in this study, and 14 of them, which included pharmacotherapy, were performed consistency analysis. (i) 64 recommendations from 14 CPGs were classified into 18 PICs. (ii) Seven PICs (38%) were consistent in direction and strength, 10 PICs (56%) were consistent in direction but inconsistent in strength, and one PIC (6%) was inconsistent in direction (hydroxychloroquine, HCQ). (iii) Sensitivity analysis tested the robustness, and the inconsistency remained high. Conclusion: The direction was highly consistent among the recommendations of pharmacotherapy for RA, but the strength was highly inconsistent. Reasons for the inconsistency need to be further investigated, and consistent recommendations could guide the pharmacotherapy of RA in clinical practice.